The Artificial Intelligence Moderation Impact Inside Tourism SMES’ Transactional Leadership and Organisational Performance: A Business Event Analysis - Ampauleng, Ampauleng; Abdullah, Salma; Mustafa, Muh. Yushar; Maulana, Achmad Amzal (Politeknik Pariwisata Makassar, Indonesia, 2025)
Literature indicates that many studies are exploring organisational performance with an emphasis on both transformational and transactional leadership styles; unfortunately, this study finds that there are few empirical studies explaining the performance of SMEs, especially tourism SMEs from developing countries, with a focus on transactional leadership style and AI. In doing so, as a research novelty of this study, it is important to investigate the moderating effect of AI on the relationship between transactional leadership style and the performance of SMEs in emerging countries. Drawing on a sample of 192 tourism small and medium-sized enterprises from an emerging country, which is Indonesia, this study applies a quantitative research approach with a purposive sampling technique and analyses the research data through a structural equation modelling approach. The findings of this study reveal that transactional leadership positively and significantly influences organisational performance, with artificial intelligence serving as a positive and significant moderator. Specifically, the presence of artificial intelligence technologies enhances the effectiveness of transactional leadership by facilitating decision-making processes and improving operational efficiency. This study identifies that the extent of artificial intelligence integration is a moderating factor, recommending that organisations must strategically adopt artificial intelligence technologies to maximise leadership effectiveness. This research is also expected to contribute theoretically and managerially to the literature on leadership, organisational study, and technology by emphasising the critical moderating role of artificial intelligence in increasing organisational outcomes, offering practical implications for leaders aiming to leverage technology for improved performance.